Dlouhodobé využití telemonitorovacího systému Diani v léčbě diabetes mellitus 1. typu - Brož, Jan; Holubová, Anna; Mužík, Jan; Vlasáková, Martina; Mužný, Miroslav; Králová, Alice; Hoskovcová, Lucie; Árská, Denisa Janíčková Ž; Arsand, Eirik; Hronová, Michaela; Urbanová, Jana; Kvapil, Milan (Vnitrni lekarstvi, 2020)
Mobile and wearable technologies offer patients with diabetes mellitus new possibilities for data collection and their more effective analysis. The Diabesdagboga smartphone application and the Diani web portal enable to collect and analyze glycaemia values, carbohydrates intake, insulin doses and the level of physical activity. The data are not only accessible in the corresponding smartphone but also automatically transferred to an Internet portal, where they may be completed by the records from an electronic pedometer and continuous glucose monitor. All these data may then be displayed in various types of graphical outputs and are available to both the patient and the physician. The case report of a patient who has used the system for almost two years shows a significant improvement in metabolic compensation (a decrease in the mean HbA1c value by 18.6 mmol/mol as compared with the previous period).
Keywords: web portal; krevní glukóza; diabetes mellitus; diabetes mellitus 1. typu; web application; inzulin; Glycated Hemoglobin A; Insulin; HbA1c; diabetes diary; telemonitoring; Diabetes Mellitus, Type 1; Blood Glucose; Humans; telemedicine; Glycated Hemoglobin; glykovaný hemoglobin; hypoglycaemia; mobile application; lidé